India-Indonesia defence cooperation : back on track? - Ristian Atriandi Supriyanto (2014)
India-Indonesia defence relations are relatively underdeveloped, notwithstanding their mutual interests. Improving bilateral dfence cooperation would require Indonesia to pay more attention to its Indian Ocean neighbourhood.